Evaluation of bacterial contamination arteriovenous fistula by direct contact for hemodialysis patients in Zawia Kidney Center - Nadia Elsayed Beshna; Amina Kalifa Elzawia (African Journal of Advanced Pure and Applied Sciences, 2024)
Dialysis is the process of removing toxins directly from the blood i.e. hemodialysis or indirectly i.e. peritoneal dialysis using diffusion across a semipermeable membrane. Chronic care patients undergoing hemodialysis for treatment of end-stage renal failure experience higher rates of healthcare-associated infection, in this study, our objective is to assess the level of contamination that reaches hemodialysis patients via the arteriovenous fistula. Hemodialysis patients are always at high risk of infection due to the nature of the hemodialysis procedure which exposes the bloodstream to the external environment, which opens up ways for bacteria, viruses, and fungi to enter the human body and cause contamination, which ultimately causes the infection. The contamination can occur from any part of the dialysis procedure, whether it is from the water being used, the machinery used, the catheter, or through direct contact with the medical staff. Most medical procedures for hemodialysis help decrease the possibility of contamination, however, the possibility of contaminations will always remain and should be monitored and regulated, which is why it is necessary to determine the cause of these contaminations and what parameters affect it.